The magnetocaloric effect in Fe80-XGdXCr8B12 alloys - Chen, Zhizhou. (2010)
Soft magnetic amorphous alloys are the new candidate material for high temperature magnetic refrigeration, which is based on the magnetocaloric effect (MCE). Gadolinium, as the benchmark material exhibiting excellent magnetocaloric properties at near room temperature is added as an alloying element to Fe-Cr-B amorphous alloys. The project was to study the magnetocaloric properties obtained by changing the gadolinium content. Binary (Fe92Cr8, Fe88B12 and Cr88B12) and ternary alloys (Fe80-xGdxCr8B12; where x = 2, 3, 10, 11, 15) were prepared by arc melting followed by melt spinning. Their structure was analyzed by Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), Differential Scanning Calorimetry (DSC). The magnetocaloric response of the alloys were characterized by Vibrating Sample Magmetometer (VSM). The amorphous character was found to be enhanced by the addition of boron. The magnetic entropy change of the Fe80-xGdxCr8B12 alloys continuously decreased as the Gd content increases, from 0.84Jkg-1K-1(x=0) to 0.19Jkg-1K-1(x=15). At the same time, the operating temperature increased away from the room temperature range by increasing Gd content, from 343K to 412K, for x=0 and 15, respectively. In conclusion, adding gadolinium into soft magnetic amorphous alloys does not enhance their magnetocaloric properties. Future research may include using crystallized alloys.